MANAGEMENT OF BIOSAFETY AT UNIVERSITY - Azra Munirah Mat Daud,; Siti Fatimah Zaharah Mohamad Fuzi,; 'Aisyah Najwa Abd Rahman, (2023)
This manual was developed by the Institutional Biosafety Committee (IBC) of Universiti Tun Hussein Onn Malaysia to provideinformation to protect workers and the surrounding environment and to comply with applicable standards and regulations. The planning and the implementation of biohazard controls to prevent laboratory associated infections and to control the spread of contamination must be a part of every laboratory activity in which biohazardous agents are used. The handling of biohazardous agents requires various precautionary measures depending on the agent(s) involved. The purpose of this manual is to provide general guidelines for evaluation, containment, and control of biohazards, categorized as degrees of risk of infection. The implementation of this manual and procedures is the responsibility of the Principal Investigator and the person in charge of each laboratory. It is essential that they seek additional advice and training when needed to conduct research in a safe manner for employees, students, and the surrounding community. To assist in this regard, the Occupational Safety, Health and Environment Office services are available at the university.